2022
DOI: 10.3390/met12111855
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Fe-W-B Amorphous Powder Prepared by Gas Atomization

Abstract: In this work, the effects of master alloy composition and annealing temperature on the amorphization and crystallization behavior of Fe-W-B powders prepared by gas atomization using compacts of Fe, W and B powder mixture were systematically studied. The results show that only the master alloy with high content of W (19.9 at.%) and B (13.6 at.%) of the six alloys studied yielded amorphous Fe-W-B powders. The alloying elements W and B are believed to have a glass-forming ability (GFA)-enhancing effect, which tog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 30 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…Fe-W-B system materials are a novel ternary boride with a TiNiSi crystal structure and a high content of W and B (73.4% and 4.3% wt%, respectively) [ 1 ]; these materials exhibit a wide range of unusual physical and chemical properties at elevated temperatures [ 2 , 3 ]. These fascinating features open a wide range of possible applications for Fe-W-B, including nuclear shielding, microwires, petrochemicals, corrosion-resistant coating, and wear-resistant materials [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fe-W-B system materials are a novel ternary boride with a TiNiSi crystal structure and a high content of W and B (73.4% and 4.3% wt%, respectively) [ 1 ]; these materials exhibit a wide range of unusual physical and chemical properties at elevated temperatures [ 2 , 3 ]. These fascinating features open a wide range of possible applications for Fe-W-B, including nuclear shielding, microwires, petrochemicals, corrosion-resistant coating, and wear-resistant materials [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gas atomization is an efficient solidification technology, extensively employed by large businesses to make high-quality metal powders. Up to now, many Fe-W-B-based alloy powders have been successfully prepared by gas atomization [ 4 ]. Furthermore, recent research has shown that optimizing the shape and distribution of the ternary boride may be achieved through including chromium (Cr) elements inside the gassing Fe-W-B alloys, thus providing a solution to improve the mechanical properties [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation